2006
DOI: 10.1249/01.mss.0000181220.03855.1c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training Resumption on Conduit Arterial Diameter in Elite Rowers

Abstract: Athletes exhibit enhanced conduit artery diameters at rest and in response to vasodilator stimuli. Despite this long-term training effect on arterial structure, resumption of training further enhances diameter, an effect that occurs within 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
5
28
1
Order By: Relevance
“…Some studies have suggested that exercise training is associated with decreased conduit arterial wall thickness (WT) in men and women (2,17), and other studies in athletes have suggested that chronic exercise induces changes in lumen size (10,18). More recently, we reported that elite squash players possess larger racquet-arm brachial artery diameters compared with their nondominant ann, whereas no such difference was present in matched nonathletic control subjects (23).…”
mentioning
confidence: 73%
“…Some studies have suggested that exercise training is associated with decreased conduit arterial wall thickness (WT) in men and women (2,17), and other studies in athletes have suggested that chronic exercise induces changes in lumen size (10,18). More recently, we reported that elite squash players possess larger racquet-arm brachial artery diameters compared with their nondominant ann, whereas no such difference was present in matched nonathletic control subjects (23).…”
mentioning
confidence: 73%
“…That such remodelling could take place within the time frame of pregnancy is supported by the following findings. First, intermittent increases in shear stress by upper-body exercise training increase brachial artery diameter in healthy, untrained individuals [39] and athletes [40] within 3 months. Chronic increases in rat mesenteric artery blood flow cause outward remodelling to normalize shear stress within 1 week [41,42].…”
Section: Table 3 Effect Of Post-release Diameter Measurement Methods Imentioning
confidence: 99%
“…For example, athletes consistently exhibit enlargement in both resistance and conduit arteries and it was recently demonstrated that, even in those with preexisting arterial remodelling, resumption of intense training is associated with further structural adaptation [48 ]. That large artery remodelling may be shear stress-mediated, and endothelium and possibly nitric oxide-dependent, is supported by classic studies [49,50] and recent reviews [47,51].…”
Section: Arterial Structurementioning
confidence: 96%